IInfluence of Mg/CTAB ratio on the structural, physicochemical properties and catalytic activity of amorphous mesoporous magnesium silicate catalysts - Tan, Kok Hou; Iqbal, Anwar; Adam, Farook; Abu Bakar, Noor Hana Hanif; Ahmad, Moballigh N.; Ahmad, Mohammad Norazmi; Yusop, Muhammad Rahimi; Pauzi, Hariy (Royal Society of Chemistry, 2019)
This study investigated the physicochemical and catalytic properties of mesoporous magnesium silicate catalysts prepared at various Mg/CTAB ratio (0.25, 0.50, 0.75 and 1.00). The XPS analysis detected a mixture of enstatite and magnesium carbonate species when the Mg/CTAB ratio was 0.25, and 0.50. A mixture of forsterite and magnesium carbonate species were detected when the Mg/CTAB ratio was 0.75 whereas for Mg/CTAB ratio of 1.00, enstatite and magnesium metasilicate species were detected. Catalyst with Mg/CTAB ratio of 1.00 indicated the highest catalytic activity in the oxidation of styrene. Its styrene conversion rate was 59.0% with 69.2% of styrene oxide (StO) selectivity. The H2O2 molecules were activated regio-specifically by the magnesium species to prevent rapid self-decomposition while promoting selective interaction with styrene. All the parameters that influence the styrene conversion and product selectivity were evaluated by using Analysis of variance (ANOVA) with Tukey’s test. Based on the ANOVA analysis, it showed that reaction time (h), Mg/CTAB ratio, styrene/H2O2 ratio, catalyst loading (mg) and temperature (°C) effects the styrene conversion and product selectivity (StO), signiﬁcantly (p< 0.05). The oxidation of styrene was well fitted to the pseudo-first-order model. The activation energy, Ea of catalyzed styrene epoxidation reaction was calculated to be 27.7 kJmol-1. The catalysts can be reused several times without any significant loss in its activity and selectivity. The results from this study will be useful in designing and developing low cost, high activity catalysts from alkaline earth metals.